ESTUDO DO SOLO ARGILOSO LATERÍTICO PARA USO EM PAVIMENTOS ECONÔMICOS - Dellaflora, Cristiano S.; Bernardi, Cândida; Borré, Gracieli; Campos, Tâmela A.; Bastos, Cezar A. B.; Wayhs, Carlos A. S. P. (Salão do Conhecimento, 2013)
Resumo